Differential buck single phase grid connected AC-DC converter with active power decoupling using a flipping Capacitor - Gottardo, Davide; De Lillo, Liliana; Empringham, Lee; Costabeber, Alessando (2017)
This paper introduces a new single-phase AC-DC converter capable of achieving independent voltage control across a dedicated power decoupling capacitor, by exploiting the same full bridge that controls the grid current in combination with two bidirectional switches, soft com¬mutated at the line frequency (ZVS). A suitable control of the capacitor voltage is used to completely decouple pulsating grid power from the DC-link, enabling the use of smaller film capacitors instead of electrolytic capacitors for power decoupling, improving reliability and increasing power density. This is achieved without additional high switching frequency devices. Furthermore, the interference occurring between rectified grid current and power decoupling capac¬itor current is exploited in order to reduce the RMS current in the full bridge, thus improving conversion efficiency.